Study of a pseudo-stationary state for a corrosion model: Existence and numerical approximation. (October 2016) - Chainais-Hillairet, Claire; Gallouët, Thomas O.
Abstract: In this paper, we consider a system of partial differential equations describing the pseudo-stationary state of a dense oxide layer. We investigate the question of existence of a solution to the system and we design a numerical scheme for its approximation. Numerical experiments with real-life data shows the efficiency of the method. Then, the analysis is fulfilled on a simplified model.